Penerapan Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Siswa Kelas X SMA Negeri 9 Kabupaten Sorong - Jumiati Sangaji; Jaharuddin Jaharuddin; Ratna Prabawati (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
This study aims to determine the application of Discover learning in improving critical thinking skills and cognitive learning outcomes of biology students of class X SMA Negeri 9 Sorong Regency. The background of this study is the low critical thinking skills and cognitive learning outcomes of students in biology learning which is still dominated by conventional methods. This study uses an experimental research method with a One Group pretest-posttest design. The assessment subjects were 12 class X students who were selected purposively. Data collection techniques included critical thinking skills tests, cognitive learning outcomes tests, and learning activity observation sheets. Data were analyzed using normality tests, homogeneity tests and paired sample t-tests at a significance level of 0.05. The results showed a significant increase in critical thinking skills and cognitive learning outcomes of students after the implementation of Discovery Learning. The average value of critical thinking skills increased from 14.50 to 83.25, while the average cognitive learning outcomes increased from 15.17 to 84.67. The t-test showed a p value 0.05 which means there was a significant difference between before and after treatment. The conclusion of this study is that Discovery Learning is effective in improving students' critical thinking skills and cognitive learning outcomes in biology learning.